Pengaruh Pelayanan Publik Terhadap Kepuasan Masyarakat Di Dinas Kependudukan Dan Pencatatan Sipil Kabupaten Bandung Barat - Riyanti Utami; Nia Sumiati; Muhammad Syukrullah Abdullah (UNIVED PRESS, Universitas Dehasen Bengkulu, 2023)
This study aims to determine the effect of public services on community satisfaction at the Population and Civil Registration Office of West Bandung Regency. This research is quantitative research. This study used a sample size of 38 people. The analysis method used is simple linear regression with the SPSS program. The results of this study state that public services have a positive and significant effect on community satisfaction at the Population and Civil Registration Office of West Bandung Regency. This is evidenced by a significant value of 0.000 <0.05 or a calculated t value of 6.047> t table value of 1.685. Thus, the research hypothesis which states that public services have a positive and significant effect on community satisfaction at the Population and Civil Registration Office of West Bandung Regency is accepted. The results of this study can add insight into the knowledge of researchers about the effect of public services on community satisfaction and the factors influencing community satisfaction at the Population and Civil Registration Office of West Bandung Regency.